Հայաստանի Հանրապետության իշխանությունների դիրքորոշումը հայկական սփյուռքի և Մեծի Տանն Կիլիկիո կաթողիկոսության հանդեպ (1990-ական թվականների առաջին կես) - Ղազարյան, Նաիրա (YSU Journal of International Affairs, 2016)
After the declaration of the Third Republic of Armenia, among the pivotal questions were the Armenian-Diaspora relations and the issue of the reunification of the two Catholicosates within the Apostolic Armenian Church. The collapse of the Soviet Union gave Armenia new opportunities to communicate on a horizontal level with Armenian Diasporas, as well as to make attempts to reunite the divided Armenian Church. However, new obstacles hindering the successful solution to the mentioned issues within a short time arose. One of the problems was the realpolitik policy conducted by the Republic of Armenia, which was not accepted by most bodies of the Diaspora, including the Catholicosate of the Great House of Cilicia, which, taking into account the issue of the “Hay Daht” (Armenian Cause) tended to make decisions and conduct policy concerning the issues of Armenians independently. The 1990s attempts to improve the Armenia-Diaspora relations, as well as the efforts at reunion of the two Catholicosates, namely the Catholicosate in Etchimiadzin and the Catholicosate in Antelias, failed mostly due to the unwillingness of the sides to make concessions on matters of national importance, or, even to recognize and accept the decisions of the other side.
Keywords: Third Republic of Armenia, the Armenian Diaspora, the Armenian Apostolic Church, Catholicosate of the Great House of Cilicia, national values, Echmiadzin, Antelias